Protocol for Management of Hyperthyroidism by Radioactive Iodine (RAIT)-SNMB Guidelines (Bangladesh Journal of Nuclear Medicine, 2017)
Abstract not availableBangladesh J. Nuclear Med. 18(1): 85-88, January 2015